THE MOST COMMONLY USED COMMUNICATION CHANNELS AS A SOURCE OF INFORMATION FOR ORGANIC FOOD BUYERS IN SERBIA - Mitić, Vladimir; Čolović, Milica (The European Journal of Applied Economics, 2025)
The organic food market has shown constant but insufficient growth in recent decades due to a number of factors, the most notable of which are high prices and insufficient consumer awareness. Better consumer awareness can be achieved by using the most effective digital and traditional marketing channels. The aim of this paper is to examine which digital and which traditional marketing channels are used by buyers to collect information about organic food. The research included 600 respondents from Serbia, and the SPSS program was used for data processing. The paper used descriptive statistics and non-parametric techniques due to the distribution of scores that deviates from normal. The research results showed that buyers of organic food rely more on digital marketing channels, primarily social networks and websites. When it comes to traditional marketing channels, TV, radio and newspapers are in first place.
Keywords: organic food, customers, digital marketing, traditional marketing, awareness